PEBANDINGAN PEMAHAMAN KONSEP ANTARA PENGGUNAAN MEDIA PROTO CIRCUIT SIMULATOR DAN VOLTSIM CIRCUIT SIMULATOR MENGGUNAKAN METODE LATIHAN SKILL DRILL MATERI LISTRIK DINAMIS PESERTA DIDIK KELAS XII IPA SMA 13 TAKALAR - Tanti, Hamdana; Suarti; Jafar, Andi ferawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aimed to evaluate students' conceptual understanding of dynamic electricity at SMA Negeri 13 Takalar by comparing the effectiveness of the Proto Circuit Simulator and Voltsim Circuit Simulator media, both implemented through the skill drill practice method. Utilizing a Posttest-Only Comparison Group Design, the study involved two classes selected via purposive sampling, designated as Experimental Group I (Proto Circuit Simulator) and Experimental Group II (Voltsim Circuit Simulator). Data were collected using a validated multiple-choice conceptual understanding test and subsequently analyzed using t-tests. The results revealed a significant difference in learning outcomes between the two groups; specifically, students taught with the Proto Circuit Simulator achieved an average score of 84.30, falling into the "Excellent" category, while those using the Voltsim Circuit Simulator reached an average of 77.91, categorized as "Good." Statistical analysis yielded a two-tailed significance value (p-value) of 0.013, which is below the 0.05 threshold, indicating that the observed difference is statistically significant. These findings demonstrate that the Proto Circuit Simulator is notably more effective than the Voltsim Circuit Simulator when paired with skill drill methods for enhancing students' conceptual grasp of dynamic electricity. Consequently, this study suggests that the interactive visual interface of the Proto Circuit Simulator provides a superior platform for students to bridge the gap between abstract electrical theories and practical conceptual application.